Application of Six Sigma in the management of caregivers of inpatients in Department of Neurology during the COVID-19 outbreak (六西格玛管理法在新型冠状病毒肺炎疫情防控期间神经内科住院患者陪护人员管理中的应用) - PAN Xi (潘习); XU Lan (徐岚); WANG Zhi (王稚) (中西医结合护理)
Objective To evaluate the application of Six Sigma in the management of caregivers of inpatients in Department of Neurology during the COVID-19 outbreak. Methods Based on the Six Sigma approach, the management process of caregivers of inpatients in Department of Neurology was divided into five phases: definition, measurement, analysis, improvement and control. The potential factors influencing the management quality were analyzed, and targeted improvement strategies were carried out from the aspect of cross-sector cooperation, process optimization, establishment of special position, tool utilization, standard training. The implementation rate of management strategy and rate of caregivers-related conflicts and complaints before and after implementation of Six Sigma were compared. Results A significant increase in qualification rate was found in the following issues such as the maximum number of the bedside caregiver, number of visitors, investigation and registration of epidemic situation of ward (P＜0. 05) . The rate of caregivers-related conflicts dropped from 16. 99% to 1. 08%, and the rate of caregivers-related complaints dropped from 3. 92% to 0, with a significant difference (P＜0. 01). Conclusion The Six Sigma is an effective tool of improving quality of caregivers management in Department of Neurology (目的 探讨六西格玛管理法在新型冠状病毒肺炎疫情防控期间神经内科住院患者陪护人员管理中的应用效果。方法 遵循六西格玛方法学基础与实施步骤, 分别从定义、测量、分析、改进和控制5个阶段对神经内科住院患者陪护人员的管理工作进行推进。对影响陪护人员管理的原因进行鱼骨图、因果矩阵分析, 找出8个关键因素, 从部门合作、流程优化、专职设立、工具利用、规范化培训等方面进行针对性改进。比较实施六西格玛管理前后陪护人员管理措施落实率及陪护相关医患纠纷和投诉发生率。结果 实施六西格玛管理法后, “患者床边陪护人员数量最多一人”、“无探视人员”、“进入病区进行疫情调查并规范登记”等多个项目合格率均较实施前显著提高, 差异有统计学意义(P＜0. 05)。陪护相关医患纠纷发生率由16. 99%降至1. 08%, 陪护相关投诉发生率由3. 92%降至0, 差异有统计学意义(P＜0. 01)。结论 六西格玛管理方法可有效提高神经内科住院患者陪护人员管理质量。)